Experiences of spiritual advocacy for land and territorial itineraries for the defense of Wiwa women’s rights in postconflict Colombia - Pastor, Lejandrina (International journal of transitional justice, 2021)
This article explores Wiwa female spiritual advocacy in the Colombian Caribbean region during the postconflict period. The methodologies and practices of indigenous communities have been underappreciated in transitional justice literature about land and property rights. This article seeks to analyze spiritual and territorial advocacy by local indigenous women for the defense of their lands and their collective rights. We examine intercultural and intersectional methodologies, rituals and recollection as strategies for clarifying the ‘truth.’ These methodologies attempt to revitalize indigenous women’s advocacy for sacred sites of the Sierra Nevada de Santa Marta affected by armed conflict. These spiritual advocacy practices are one expression of the Law of Origin, the customary law as a form of telling the truth. Here, we explain how participatory action research should be used to include female indigenous techniques and conduct ethnographic observations.